Using essence of Islamic architecture as a reference for shapping today’s contemporary Islamic architecture - Soomro, Ali Raza; Awada, Hasan M.I. (Sci.Int.(Lahore), 2014)

(untitled)
This paper presents Islamic architecture through its essence, by grasping its characteristics and the depth of its philosophy for shaping Contemporary Islamic Composition. It focuses on two issues: The unchangeable combination of the essence of Islamic Architecture. Secondly, the issue of addressing the question of how to shape a contemporary design from the essence of the Islamic architecture and convert it into architectural relations. The findings suggest that the definition of the essence of Islamic architecture and definition of the contemporary design are based on values and relations not on just the copy of elements in its traditional image, even if they are edited by new materials but they are still traditions in their sense and combination. In addition, the paper presents the essence of Islamic architecture is a composition of authenticity of the traditions to interact with progress and meeting of continuous growing needs of human kind.